2014
DOI: 10.1002/ppul.23000
|View full text |Cite
|
Sign up to set email alerts
|

High flow nasal cannula (HFNC) with Heliox decreases diaphragmatic injury in a newborn porcine lung injury model

Abstract: Background High flow nasal cannula (HFNC) improves ventilation by washing out nasopharyngeal dead space while delivering oxygen. Heliox (Helium-oxygen gas mixture), a low density gas mixture, decreases resistance to airflow, reduces the work of breathing and facilitates distribution of inspired gas. Excessive lung work and potential injury increases the workload on the immature diaphragm predisposing the muscle to fatigue and can lead to inflammatory and oxidative stress, thereby contributing to impaired diaph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…A study in an animal model found that increased diaphragm load, expressed by high voltage Edi max , is associated with damage to its sarcomeres 25 . In a porcine model of acute lung injury, high flow nasal cannula (HFNC) with heliox demonstrated a protective effect towards the diaphragm 26 . The significant and rapid decrease of Edi voltage after introduction of heliox suggests that the change of breathing mixture to heliox has direct influences on respiratory function.…”
Section: Discussionmentioning
confidence: 99%
“…A study in an animal model found that increased diaphragm load, expressed by high voltage Edi max , is associated with damage to its sarcomeres 25 . In a porcine model of acute lung injury, high flow nasal cannula (HFNC) with heliox demonstrated a protective effect towards the diaphragm 26 . The significant and rapid decrease of Edi voltage after introduction of heliox suggests that the change of breathing mixture to heliox has direct influences on respiratory function.…”
Section: Discussionmentioning
confidence: 99%
“…Heliox ventilation was reported to reduce respiratory effort, diaphragmatic load and display protective effects against atelectasis and airway collapse. In addition, it facilitates the distribution of respiratory gases in narrow and/or constricted airways (17, [23][24][25]. Helium-oxygen may allow better penetration into the peripheral parts of the lungs and improve ventilation/perfusion ratio.…”
Section: Physiological Effects Of Helioxmentioning
confidence: 99%
“…Another modality of respiratory support that was shown to be safe and more effective than standard oxygen therapy in infants with bronchiolitis is high flow nasal cannula (HFNC) ( 37 , 38 ). Considering this fact and encouraging results of a study in which HFNC with Heliox utilized in animal models of lung injury resulted in reduced work or breathing and less lung inflammation it seems that helium-oxygen high flow therapy may be an interesting alternative to nCPAP ( 24 ). There was an attempt to assess Heliox HFNC in bronchiolitis in an American trial that was terminated in 2019 (NCT02373683).…”
Section: Clinical Applications Of Helioxmentioning
confidence: 99%
“…Preclinical evidence suggests that heliox combined with high-flow nasal cannula decreases work of breathing and attenuates diaphragmatic injury and fatigue [63]. The role of heliox in infants with skeletal dysplasia and airway obstruction is yet to be explored and holds potential.…”
Section: Treatment Strategiesmentioning
confidence: 99%